The great leveler: violence and the history of inequality from the Stone Age to the twenty-first century - Scheidel, Walter (Princeton classics, 2025)
"How only violence and catastrophes have consistently reduced inequality throughout world history. Are mass violence and catastrophes the only forces that can seriously decrease economic inequality? To judge by thousands of years of history, the answer is yes. Tracing the global history of inequality from the Stone Age to today, Walter Scheidel shows that inequality never dies peacefully. Inequality declines when carnage and disaster strike and increases when peace and stability return. The Great Leveler is the first book to chart the crucial role of violent shocks in reducing inequality over the full sweep of human history around the world. Ever since humans began to farm, herd livestock, and pass on their assets to future generations, economic inequality has been a defining feature of civilization. Over thousands of years, only violent events have significantly lessened inequality. The "Four Horsemen" of leveling--mass-mobilization warfare, transformative revolutions, state collapse, and catastrophic plagues--have repeatedly destroyed the fortunes of the rich. Scheidel identifies and examines these processes, from the crises of the earliest civilizations to the cataclysmic world wars and communist revolutions of the twentieth century. Today, the violence that reduced inequality in the past seems to have diminished, and that is a good thing. But it casts serious doubt on the prospects for a more equal future. An essential contribution to the debate about inequality, The Great Leveler provides important new insights about why inequality is so persistent--and why it is unlikely to decline anytime soon."--Provided by publisher